The implementation of the early warning system for the paradigm shift towards efficient and collaborative project management - Manyari, Ahmed (2020)
In this article, the authors discuss how the implantation of an Early Warning System in construction contracts can generate the necessary incentives for the emergence of a paradigm shift in the field of project and work management: from a confrontational management toward a collaborative and efficient management. The authors analyze what are the elements, discuss the elements, benefits and conditions for the implementation of an Early Warning system.